Penambahbaikan Sistem Perparitan yang Menyebabkan Banjir Kilat di Jalan Kluang, Batu Pahat, Johor - Ahmad Ruslan, Muhammad Akmal Ilham; Sarpin, Norliana; Ta Wee, Seow; Mohamed, Sulzakimin; Shafii, Haryati (Research in Management of Technology and Business, 2023)
In Malaysia, the occurrence of flash floods is a phenomenon that is no longer unfamiliar to the local community. Flash floods often occur due to natural combinations and consequence’s from human actions. Problems with flash floods in a study area have resulted in daily disruptions to the population, property damage, traffic congestion, and many more. In this context, this study was conducted to identify the drainage system problems that caused flash floods and propose drainage system improvements to address the problem of flash floods on Kluang Road Section 4.0 to Section 6.3, Batu Pahat, Johor. This study is conducted with qualitative methods using semi-structured interviews. The respondents are representative from the Department of Irrigation and Drainage (JPS) and the Department of Works (JKR) of Batu Pahat District, Johor. Meanwhile, the data was analysed using the content analysis method. The findings of the study found that the main problems with the drainage system that cause flash floods to occur are due to monsoon drainage system problems, land drainage system maintenance problems, conventional drainage problems and unplanned development impacting the drainage system which ultimately causes flash floods to occur. Meanwhile, the proposed improvement mentioned is to increase the number of frequencies to maintain the drainage system, upgrade the soil drainage system and make improvements to the conventional drainage system. Therefore, this study is expected to provide useful and beneficial information to all parties. This study is also expected to give a clear picture of the drainage system problems that occur in Kluang Road in Batu Pahat that cause the occurrence of flash floods.